2011
DOI: 10.1021/jf201052u
|View full text |Cite
|
Sign up to set email alerts
|

Allium Species from Central and Southwest Asia Are Rich Sources of Marasmin

Abstract: Marasmin, which is especially known from the two South African species Tulbaghia alliacea and Tulbaghia violacea , but was also described for the garlic mushroom Marasmius alliaceus , is the precursor of the thiosulfinate marasmicin. Marasmicin has attracted considerable attention because of its antifungal and tuberculostatic activities. However, many Allium species of the subgenus Melanocrommyum, especially Allium suworowii , are also very rich in marasmin. A. suworowii revealed concentrations of marasmin up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 19 publications
0
7
0
1
Order By: Relevance
“…1 seems to be present abundantly in all Allioideae species, including members of the Allium subgenera Melanocrommyum, Caloscordum, and Nectaroscordum. 4,[6][7][8][9][10][13][14][15][16][17]37,38 On the contrary, the present study revealed that Tulbaghioideae and Gilliesioideae plants accumulate 1 only at trace levels (if at all) and 11 is the principal derivative present in these species. Furthermore, the threecarbon side chain derivatives [i.e., 3, 4, and propiin (5)] are present only in Allium species, excluding members of the subgenera Nectaroscordum, Caloscordum, and Melanocrommyum which do not contain 3−5 at significant levels.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 71%
See 1 more Smart Citation
“…1 seems to be present abundantly in all Allioideae species, including members of the Allium subgenera Melanocrommyum, Caloscordum, and Nectaroscordum. 4,[6][7][8][9][10][13][14][15][16][17]37,38 On the contrary, the present study revealed that Tulbaghioideae and Gilliesioideae plants accumulate 1 only at trace levels (if at all) and 11 is the principal derivative present in these species. Furthermore, the threecarbon side chain derivatives [i.e., 3, 4, and propiin (5)] are present only in Allium species, excluding members of the subgenera Nectaroscordum, Caloscordum, and Melanocrommyum which do not contain 3−5 at significant levels.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 71%
“…siculum and A. tripedale) are significantly distinct from all other alliaceous species in their ability to synthesize two four-carbon side chain derivatives, namely, S -butyl- and ( E )- S -(1-butenyl)cysteine S- oxides ( 7 and 8 , butiin and homoisoalliin, respectively). Finally, subgenus Melanocrommyum species are characterized by the presence of 11 and two unusual heterocyclic derivatives, i.e., S -(2-pyrrolyl)cysteine S -oxide ( 9 ) and S -(2-pyridyl)cysteine N -oxide ( 10 ). ,, …”
Section: Resultsmentioning
confidence: 99%
“…Allium L. is one of the largest genera in the family of the Amaryllidaceae, encompassing over 900 species [1,2]. The main center of its diversity is central Asia, including the territory of Iran and the Mediterranean, while the second distribution center for garlic and many Allium is western North America [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The genus Allium L. is one of the largest monocotyledonous genera with c. 900 species distributed world-wide (Govaerts et al 2013, Keusgen et al 2011). The genus was formerly included in the Liliaceae family, but the (APG)Angiosperm Phylogeny Group reassessed the taxonomic position of this genus and finally Allium was placed in the Amaryllidaceae family (APG III 2009).…”
Section: Introductionmentioning
confidence: 99%